Modeling of a fan-supplied flat-tube heat exchanger exposed to non-uniform frost growth. (March 2017) - Breque, Florent; Nemer, Maroun
Highlights: A pseudo 3D model of a fan-supplied MCHX under frosting conditions is presented. A new approach with respect to air pressure loss prediction is proposed. A new correlation is developed to model frost effects on the friction factor. The model predicts the experimental data with an RMS deviation less than 3.8%. Abstract: Reversible heat pumps for electric vehicles are being developed by the car industry to address cabin heating and improve energy efficiency compared to electric heaters. For this new application, the front, louvered-fin, microchannel heat exchanger (MCHX or flat-tube heat exchanger) of the A/C system happens to operate as an evaporator under frosting conditions. MCHX are particularly sensitive to frosting, and a model is required to improve the design. This paper presents a dynamic pseudo 3D model of a fan-supplied MCHX which predicts non-uniform frost growth, air pressure losses, airflow rate and thus, thermal performances. The air pressure losses are computed considering the maximum frost thickness along each air channel. A correlation was developed to take into account frost effects on the friction factor. The model was validated against ad hoc experimental data and was also able to predict experimental data from the literature.